Exploring the Link between Micronutrients and Phytoplankton in the Southern Ocean during the 2007 Austral Summer - Hassler, Christel; Sinoir, Marie; Clementson, Lesley; Butler, Edward C. (Frontiers in Microbiology, 2012)
Bottle assays and large-scale fertilization experiments have demonstrated that, in the Southern Ocean, iron often controls the biomass and the biodiversity of primary producers. To grow, phytoplankton need numerous other trace metals (micronutrients) required for the activity of key enzymes and other intracellular functions. However, little is known of the potential these other trace elements have to limit the growth of phytoplankton in the Southern Ocean. This study, investigates whether micronutrients other than iron (Zn, Co, Cu, Cd, Ni) need to be considered as parameters for controlling the phytoplankton growth from the Australian Subantarctic to the Polar Frontal Zones during the austral summer 2007. Analysis of nutrient disappearance ratios, suggested differential zones in phytoplankton growth control in the study region with a most intense phytoplankton growth limitation between 49 and 50°S. Comparison of micronutrient disappearance ratios, metal distribution, and biomarker pigments used to identify dominating phytoplankton groups, demonstrated that a complex interaction between Fe, Zn, and Co might exist in the study region. Although iron remains the pivotal micronutrient for phytoplankton growth and community structure, Zn and Co are also important for the nutrition and the growth of most of the dominating phytoplankton groups in the Subantarctic Zone region. Understanding of the parameters controlling phytoplankton is paramount, as it affects the functioning of the Southern Ocean, its marine resources and ultimately the global carbon cycle.